Physiological responses to ramp-incremental cycling tests performed at three simulated altitudes: a randomized crossover trial - Beever, A. T.; Zhuang, A. Y.; Aboodarda, S. J.; Murias, J. M.; MacInnis, M. J. (Applied Physiology, Nutrition, and Metabolism, 2022)
Hypoxia negatively impacts aerobic exercise, but exercise testing in hypoxia has not been studied comprehensively. To determine the effects of simulated altitude on the gas exchange threshold (GET), respiratory compensation point (RCP), and maximal oxygen uptake (VO2max), 24 participants (mean [SD]; 26 [4] years; 171.6 [9.7] cm; 69.2 [11.9] kg) acclimatized to mild altitude (MILD; ~1100 m) performed three cycling ramp-incremental exercise tests (with verification stages performed at 110% of peak power output (PPO)) in simulated altitudes of 0 m (sea level, SL), 1111 m (MILD), and 2222 m (moderate altitude, MOD), in a randomized order. There were significant effects of condition (i.e., fraction of inspired oxygen [F_I O_2) for GET (p = 0.001), RCP (p < 0.001), VO2max (p < 0.001), and PPO (p < 0.001). The VO2 corresponding to GET and RCP (mL·kg-1·min-1) in MOD (24.1 [4.3]; 37.3 [5.1]) were significantly lower (p < 0.05) compared to SL (27.1 [4.4]; 41.8 [6.6]) and MILD (26.8 [5.7]; 40.7 [7.3]) but similar (p > 0.05) between SL and MILD. For each increase in simulated altitude, VO2max (SL: 51.3 [7.4]; MILD: 50.0 [7.6]; MOD: 47.3 [7.1] mL·kg-1·min-1) and PPO (SL: 332 [80]; MILD: 327 [78]; SL: 316 [76] W) decreased significantly (p < 0.05 for all comparisons). VO2max values from the verification stage were lower than those measured during the ramp-incremental test (p = 0.017). Overall, a mild simulated altitude had a significant effect on VO2max and PPO but not GET and RCP, MOD decreased all four variables, and the inclusion of a verification stage had little effect on the determination of VO2max in a group of young healthy adults regardless of the FIO2.